Promoting sustainable agricultural intensification and crowdsourcing plot information - Laso Bayas, Juan Carlos; Gardeazábal Monsalve, Andrea; Karner, Mathias; Vargas, Luis; Folberth, Christian; Skalsky, Rastislav; Balkovič, Juraj; Delerce, Sylvain Jean; Crespo Cuaresma, Jesus; Hlouskova, Jaroslava; Verhulst, Nele; See, Linda; et al. (International Institute for Applied Systems Analysis, 2020)
Provision of adequate and timely information to farmers on the ground means optimizing crop production decisions, reducing costs and eliminating adverse effects of overuse of agricultural inputs, e.g. fertilizer.